Using computer games to improve secondary school students’ vocabulary acquisition in English - Letchumanan, Kanthimathi; Tan, Bee Hoon (Universiti Putra Malaysia Press, 2012)
This exploratory study aims to investigate if computer games can expand learners’ vocabulary and improve their writing performance. In testing the research instruments and procedure of a larger project, this pilot study employed only ten Form Four students who had voluntarily taken part in this study, and they were exposed to two different methods of acquiring vocabulary over a period of fourteen weeks. The two methods of vocabulary acquisition were computer games and traditional vocabulary strategies. The first method involved the subjects playing computer vocabulary games from the Internet for seven weeks. In the second method they employed traditional vocabulary strategies such as using a dictionary, contextual clues and semantic mapping for the next seven weeks. The extent of the subjects’ vocabulary acquisition in the two methods was measured by using the pre and post vocabulary tests and two written essays. Results indicate a significant difference between the pre and post vocabulary tests. However, no significant difference was found between the two essays in terms of vocabulary richness. Such results might be attributable to the short duration of the treatment.